Pengaruh tingkat inflasi dan suku bunga terhadap nilai tukar rupiah - Sutrisno Sutrisno; Dr. Michael, MS Michael; Andriawan Kustiawan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Analysis of the Profits of Chicken Noodle Traders in Tenggarong District, under the guidance of Dr. Jiuhardi, MM as a first advisor and Mrs. Muliati, SE, M.Sc as second advisor. The purpose of this study was to determine the relationship between the characteristics of respondents with merchant acceptance and to analyze the profits of chicken noodle business for traders. Research data collection using survey methods and samples used as many as 31 traders chicken noodle. This study uses the Chi Square test to analyze the characteristics of respondents, profit analysis and R / C ratio analysis to analyze the feasibility of chicken noodle business.. The results showed that the characteristics of respondents including age, sex, education and the number of dependents do not have a significant relationship with the reception, while the characteristics of respondents consisting of a long effort and daily capital has a significant relationship with the merchant acceptance. R / C Ratio calculation results have a value of more than 1, which means the chicken noodle business is feasible and has provided benefits for traders.